(untitled) (Journal of Engineering, 2024)
Travel-time reliability is a crucial performance measure for transportation systems. This research aims to estimate travel time and predict delay time on three routes in Baghdad city using GPS devices: Safi Al-Den Street, Palestine Street, and the Army Channel Expressway. The study was conducted northward from 7:00 a.m. to 9:00 p.m. Reliability indices for the first and second routes with signalized intersections, including buffer index, travel time index, and 95th percentile travel time, were determined. Safi Al-Den Street’s buffer time index for links 1 to 3 is approximately 44.75%, 39.87%, and 39.12%, respectively. The highest travel time index value is observed in link 3 at 8.9%. Link 1 has the longest 95% travel time at 659 seconds. Palestine Street shows a high buffer time index in links 1 and 3 at around 32.39% and 24.65%, respectively. The highest travel time index is in link 3 at 6.84%, attributed to congestion from increased educational, medical, and commercial trips. The longest 95% travel time is 430 seconds in link 7. This study offers valuable insights into the reliability of travel time in urban corridors in Baghdad city, aiding transportation planners and engineers in making informed decisions on traffic management, infrastructure development, and policy-making.